Dissecting the Influence of Products and Digital Marketing on Purchase Decisions: The Pivotal Role of Consumer Satisfaction (Case Study of Kampung Lele Kediri) - Kurniawati, Endah; Ayuanti, Rafikhein Novia (Asian Journal of Management Analytics, 2025)
This study investigates the impact of product quality and digital marketing on consumers' purchasing decisions in Kampung Lele Kediri, mediated by satisfaction. Findings reveal that while product quality significantly enhances satisfaction, it doesn't directly drive purchases, suggesting other influencing factors. Digital marketing, meanwhile, shows no significant impact. To improve, Kampung Lele Kediri should refine pricing and marketing strategies, bolster digital marketing efforts through training and engaging content, and complement product quality improvements with loyalty programs and enhanced service. This research offers valuable insights for businesses and policymakers to formulate more effective strategies.